Comparison of growth and survival of snakehead, Channa striatus (Bloch) using commercial pellet and traditional trash fish - Abdl Ghani, Shahrul Ruzaidi (2013)
An experiment of selected diets was carried out onChannastriatus fingerlings to compare the growth and survival in captive tank. The diets used for different treatments were trash fish (T1), commercial pellet (T2) and commercial pellet combines with trash fish (T3). The best weight gain (1143.7±100 g) of C. striatuswas observed in T2. The result of this study shows, treatment 2 (T2) yield the best growth performance with the lowest FCR among treatments and had high value of survivality with no significant difference among them. It is recommended in the commercial scale C. striatusfarming.